2021
DOI: 10.1177/20587384211023670
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of allergen profile in patients sensitized to canine allergen and potential Can f 5 cross-reactivity with human PSA

Abstract: Can f 5 allergy and possible cross-reactivity with human semen in which there are significant amounts of prostate-specific antigen (PSA) are particularly interesting aspects of allergy to dog. The objective of the study was to confirm cross-reactivity between human PSA and Can f 5 in a study of canine sensitised women. A total of 100 women (aged 18–73, 41 on average) with a positive history of animal fur allergy or positive skin prick tests to canine allergens were selected. Levels of Immunoglobulin E (IgE) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Research on modifying cytological profiles in infertile women would be interesting, but difficult to achieve because of bioethical concerns. 1 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Research on modifying cytological profiles in infertile women would be interesting, but difficult to achieve because of bioethical concerns. 1 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The suspicion of cross-reactivity between the human PSA and the Can f 5 canine allergen was postulated earlier [ 14 , 15 ]. In our previous publication, we presented the results of an inhibition test in assessing the cross-reactivity between anti-Can f 5 IgE antibodies and human PSA [ 17 ]. The protocols currently presented are an extensive, full version of that experience.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier publication [ 17 ], we demonstrated the ability of anti-Can f 5 IgE antibodies to partially bind human PSA. This property is likely due to the similarity between the canine kallikrein molecule and human prostatic kallikrein, which results in the cross-reactivity of antibodies specific to these proteins [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Prostatic kallikrein Can f 5 is an androgen-regulated protein expressed in the prostate and hence is present only in male dogs, and there is no strong cross-reactivity between Can f 5 and the extracts from other furry animals. 24 , 30 Lipocalins, as an important sensitizing protein in animals, can often predict the development of IgE cross reactions based on sequence identity, 29 Previous studies have also shown that cross-reactivity occurs only between those lipocalins with a high degree of homology. 11 , 31 However, since only a limited panel of lipocalin components of cat were detected in this study, and no more lipocalin components of other furry animals were commercially available for detection, it may lead to the differences between the results of lipocalin in this study and previous studies.…”
Section: Discussionmentioning
confidence: 99%